Carbonization and agricultural productivity in Bhutan: Investigating the impact of crops production, fertilizer usage, and employment on CO2 emissions. (15th November 2022) - Rehman, Abdul; Alam, Mohammad Mahtab; Alvarado, Rafael; Işık, Cem; Ahmad, Fayyaz; Cismas, Laura Mariana; Mungiu Pupazan, Mariana Claudia
Abstract: Investigating the important role played by agriculture and carbon dioxide emission is crucial from environmentally sustainable agriculture production. The present analysis determined the impact of crops production, fertilizers use, land used for the crops production, and employment in agriculture on CO2 emission in Bhutan by taking the annual data varies from 1980 to 2020. Study utilized the two unit root testing for the stationarity purpose, while a symmetric (ARDL) technique is employed to check the variables influence on CO2 emission with the estimation of short-run and long-run. Additionally, the study also utilized the Stepwise and Robust Least Squares to explore the interaction amid variables. The crops productivity and land used for the crops showed a constructive relation to carbon dioxide emission, while fertilizer consumption and employment in agriculture has adverse connection to CO2 emission in Bhutan via long-run analysis. The results of short-run described that variables crops production and land used for these crops has productive influence to CO2 emission, while the variables fertilizers usage and employment in agriculture revealed a negative linkage to CO2 emission. Furthermore, the findings of Stepwise least squares and Robust least squares explore that crops production and land used for crops production has positive, while remaining variables has adversative association to carbonization. The findings suggest that strong strategies and plans are required from the Bhutanese government to decrease the CO2 emission in directive to upsurge the agricultural productivity. Highlights: We determined the impact of crops production, fertilizers use, land used for the crops production, and employment in agriculture on CO2 emission. Study used ARDL, Stepwise and Robust Least Squares techniques to encounter the variables influence on CO2 emission. Crops productivity and land used for the crops exposed a positive impact on carbon emission. Fertilizer consumption and employment in agriculture show an adverse connection to carbon emission.